Intravenous Infusion of Bone Marrow–Derived Mesenchymal Stem Cells Reduces Erectile Dysfunction Following Cavernous Nerve Injury in Rats - Yohei Matsuda, MD; Masanori Sasaki, MD, PhD; Yuko Kataoka-Sasaki, MD, PhD; Akio Takayanagi, MD, PhD; Ko Kobayashi, MD, PhD; Shinichi Oka, MD, PhD; Masahito Nakazaki, MD, PhD; Naoya Masumori, MD, PhD; Jeffery D. Kocsis, PhD; Osamu Honmou, MD, PhD (Sexual Medicine, 2018)
Introduction: Intravenous preload (delivered before cavernous nerve [CN] injury) of bone marrow–derived mesenchymal stem cells (MSCs) can prevent or decrease postoperative erectile dysfunction (J Sex Med 2015;12:1713–1721). In the present study, the potential therapeutic effects of intravenously administered MSCs on postoperative erectile dysfunction were evaluated in a rat model of CN injury. Methods: Male Sprague-Dawley rats were randomized into 2 groups after electric CN injury. Intravenous infusion of bone marrow–derived MSCs (1.0 × 106 cells in Dulbecco's modified Eagle's medium 1 mL) or vehicle (Dulbecco's modified Eagle's medium 1 mL) was performed 3 hours after electrocautery-induced CN injury. Main Outcome Measures: To assess erectile function, we measured intracavernous pressure at 4 weeks after MSC or vehicle infusion. Histologic examinations were performed to investigate neuronal innervation and inhibition of smooth muscle atrophy. Green fluorescent protein–positive bone marrow–derived MSCs were used for cell tracking. To investigate mRNA expression levels of neurotrophins in the major pelvic ganglia (MPGs), quantitative real-time polymerase chain reaction was performed. Results: The decrease of intracavernous pressure corrected for arterial pressure and area under the curve of intracavernous pressure in the bone marrow–derived MSC group was significantly lower than that in the vehicle group at 4 weeks after infusion (P < .05). Retrograde neuronal tracing indicated that the MSC group had a larger number of FluoroGold-positive neurons in the MPGs compared with the vehicle group. The ratio of smooth muscle to collagen in the MSC group was significantly higher than in the vehicle group. Green fluorescent protein–positive bone marrow–derived MSCs were detected in the MPGs and injured CNs using confocal microscopy, indicating homing of cells to the MPGs and injured CNs. Brain-derived neurotrophic factor and glial cell-derived neurotrophic factor expression levels in the MPGs were significantly higher in the MSC group than in the vehicle group (P < .01). Conclusion: Intravenous infusion of bone marrow–derived MSCs after CN injury might have therapeutic efficacy in experimental erectile dysfunction. Matsuda Y, Sasaki M, Kataoka-Sasaki Y, et al. Intravenous Infusion of Bone Marrow–Derived Mesenchymal Stem Cells Reduces Erectile Dysfunction Following Cavernous Nerve Injury in Rats. Sex Med 2018;6:49–57.